Kinetics of magnesium sulfite oxidation catalyzed by cobalt using a straw/sludge substrate as support. Issue 1 (4th May 2018) - Wang, Lidong; Qi, Dan; Zhang, Guangman; Li, Danyang; Qi, Tieyue; Liu, Jie; Li, Meng; Ma, Yongliang
Abstract : Oxidation of magnesium sulfite is a key step in the wet magnesia desulfurization. Using the mixture of waste corn stalk (CS) and activated sludge (AS) as a support, the cobalt‐based catalyst was prepared by the impregnation method to promote the oxidation rate. The results indicated that the catalysis performance is highly dependent on the ratio of CS/AS in which 8:2 is the optimal, and that with the cobalt loading of 0.6% dominates the catalytic activity. The physicochemical properties of catalyst were identified by FTIR, XRD, TEM and XPS to reveal the catalytic mechanism. The catalyzed oxidation kinetics of magnesium sulfite was investigated in a bubbling tank. The reaction orders with respect to catalyst, magnesium sulfite and oxygen were achieved to be 0.75, 0 and 0.67, respectively. The apparent activation energy were derived as 34.9 kJ·mol −1 . Integrating with a three‐phase reaction model, it was inferred that the overall oxidation is controlled by the inner diffusion of oxygen. The research results can serve as a reference for the development of low‐cost catalytic techniques for the magnesia desulfurization. © 2018 American Institute of Chemical Engineers Environ Prog, 38: 201–207, 2019